The Morphology of Paca (Cuniculus paca) Testis with High Dose of Letrozole an Aromatase Inhibitor - Simoes, Luciana Senna; Castro Sasahara, Tais Harumi de; Favaron, Phelipe Oliveira; Leal, Leonardo Martins; Oliveira, Fabricio Singaretti de [UNESP]; Fratini, Paula; Berger, Trish; Fernandes Machado, Marcia Rita [UNESP]; Miglino, Maria Angelica (Soc Chilena Anatomia, 2020)
The study reported the influence of the high and acute dose of Letrozole on the testis morphology in paca (Cuniculus paca), an aromatase inhibitor that reduces the endogenous estrogen, the essential hormone for spennatogenesis. Morphological changes were observed in seminiferous epithelium with germ cells with apoptotic characteristics and presence of vacuoles and nuclei in pycnose.
Keywords: Gonadal; Toxic; Spermatogenesis